Enterprise architects : masters of the unseen city - Tinsley, Thomas A. ([S.l.] : Thomas A. Tinsley, 2009)
This book presents an approach to discover the corporate Enterprise Architecture by collecting and building an information repository that contains the metadata of the data and processes of an organization. This approach and techniques are presented to encourage other Enterprise Architects to focus on bringing visualization to their organization. The book demonstrates this visualization with over 100 color diagrams automatically generated from a managed repository.
Includes index.
oif 17/09/14
Loan
Keywords: Enterprise architecture; Information technology -- Management; Information resources management; Diffusion of innovations; Organizational change; Information society